2022
DOI: 10.3389/fgene.2022.927519
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Breast Cancer and Blood-Based Methylation of CD160, ISYNA1 and RAD51B in the Chinese Population

Abstract: Recent studies have identified DNA methylation signatures in the white blood cells as potential biomarkers for breast cancer (BC) in the European population. Here, we investigated the association between BC and blood-based methylation of cluster of differentiation 160 (CD160), inositol-3-phosphate synthase 1 (ISYNA1) and RAD51 paralog B (RAD51B) genes in the Chinese population. Peripheral blood samples were collected from two independent case-control studies with a total of 272 sporadic early-stage BC cases (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…However, to understand the complete mechanism underlying CD160-mediated anti-apoptotic effects, further investigation is needed. Additionally, a recent study demonstrated that CD160 hypomethylation in blood cells was correlated with breast cancer in a Chinese population ( 16 ). Therefore, further studies should be conducted to demonstrate the mechanisms regulating CD160 expression in both CLL B cells and the neighboring cells that reside in the microenvironment (e.g., T cells and NK cells) and whether this expression is mediated by genetic or epigenetic alterations.…”
Section: Cd160 Expression and Dual Function In Cllmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to understand the complete mechanism underlying CD160-mediated anti-apoptotic effects, further investigation is needed. Additionally, a recent study demonstrated that CD160 hypomethylation in blood cells was correlated with breast cancer in a Chinese population ( 16 ). Therefore, further studies should be conducted to demonstrate the mechanisms regulating CD160 expression in both CLL B cells and the neighboring cells that reside in the microenvironment (e.g., T cells and NK cells) and whether this expression is mediated by genetic or epigenetic alterations.…”
Section: Cd160 Expression and Dual Function In Cllmentioning
confidence: 99%
“…Thus, CD160 is involved in antitumor immunity ( 3 ) and protection during chronic infections ( 8 , 9 ). In general, CD160 has been reported to be involved in the development of some pathologies, including autoimmune diseases ( 10 ), inflammatory diseases ( 11 ), atherosclerosis ( 12 ), retinal vascular diseases ( 7 ), chronic viral infections ( 8 , 13 15 ), and cancer ( 16 18 ).…”
Section: Introductionmentioning
confidence: 99%